2017
DOI: 10.1063/1.4979975
|View full text |Cite
|
Sign up to set email alerts
|

Broadening microwave absorption via a multi-domain structure

Abstract: Materials with a high saturation magnetization have gained increasing attention in the field of microwave absorption; therefore, the magnetization value depends on the magnetic configuration inside them. However, the broad-band absorption in the range of microwave frequency (2-18 GHz) is a great challenge. Herein, the three-dimensional (3D) Fe/C hollow microspheres are constructed by iron nanocrystals permeating inside carbon matrix with a saturation magnetization of 340 emu/g, which is 1.55 times as that of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 39 publications
0
27
0
1
Order By: Relevance
“…It is known that the magnetic domain aligment in the presence of EM field asschematically shown in Fig. 15 and consequent hysteresis that developes during realignment would result in loss [44,45]. Also, peaks can be seen in Fig.…”
Section: Resultsmentioning
confidence: 91%
“…It is known that the magnetic domain aligment in the presence of EM field asschematically shown in Fig. 15 and consequent hysteresis that developes during realignment would result in loss [44,45]. Also, peaks can be seen in Fig.…”
Section: Resultsmentioning
confidence: 91%
“…The presence of pinning on the surface of the particle removes degeneracy between the lowest exchange mode, μ 10 , and the uniform ferromagnetic resonance and increases the sensitivity of the exchange modes to variations in shell size and thickness. When the internal energies favor highly nonuniform magnetization states, it has been shown that multidomain magnetization configurations can also play an important role in broadening EMW absorption [44]. Nonuniform magnetization configurations are shown to exhibit multiple high-frequency modes that can reach frequencies of 20 GHz for Fe shells [45,46] and can potentially manifest as several high-frequency resonance bands in the microwave absorption spectrum.…”
Section: Volume Loading (%)mentioning
confidence: 99%
“…( 除此之外, 还有一些机制更加复杂的相互作用, 比如畴壁共振、畴壁位移、多畴耦合机理、电磁参数 表 的 非 线 性 共 振 [45] 等 . 比 如 Liu 等 人 [46] 研 究 发 现 , 波材料 [47] 对于可见光透明, 能够做到非常薄, 在50 nm的银网上复合一层石墨烯, 其微波屏蔽性能有显 著 的 提 升 . 而 另 一 种 过 渡 金 属 碳 化 物 (MXenes) [48] , 在几个微米的厚度条件下即可取得很好的屏蔽性能.…”
Section: 个材料的性能表现也会有明显影响 比如 Xu课题unclassified